CD30 Expression and Its Correlation with Clinicopathologic Features in Indonesian Diffuse Large B-Cell Lymphoma - Reynelda Santoso, Maria; Suci Hardianti, Mardiah; Indrawati, Indrawati; Anggorowati, Nungki (Asian Pacific Journal of Cancer Biology, 2020)
Background: Diffuse large B-cell lymphoma (DLBCL) is the most common subtype (68.2%) of B cells Non Hodgkin Lymphoma in Indonesia. This tumor heterogeneity is characterized by a variety of clinical conditions, morphology, genetic profiles, therapeutic response, prognosis and survival. Recent studies have shown that CD30 immunohistochemical staining also plays an important role in determining the therapy and prognosis of DLBCL disease. CD30 can also be expressed in DLBCL in approximately 9.5-40%. However, CD30 expression and clinicopathological characteristics of Indonesian DLBCL remain unknown. This study aimed to determine the prevalence of CD30 expression and its correlation with clinicopathological characteristics of Indonesian DLBCL patients. Methods: During a study period of four years, a total of 104 FFPE of DLBCL cases were collected from Anatomical Pathology Department, Sardjito Hospital, Special Region of Yogyakarta, Indonesia. CD30 expression was studied using immunohistochemical techniques (Mouse monoclonal antibody MoAb CD30 cell marque Ber-H2). Correlations between positive CD30 immunoreactivity and clinicopathological characteristics in DLBCL patients were statistically analyzed using chi-square tests. Result: Positivity rate of CD30 expression in 104 DLBCL samples was 13.5% (14/104) using cutoff value of 0% while using a 20% cutoff, it was 1.9% (2/104). Statistical associations of positive CD30 expression and clinicopathological characteristics (age, sex, Ann Arbor stage, extranodal involvement and morphological variants) were not significant (p > 0.05). Conclusions: The prevalence of positive CD30 expression in Indonesian DLBCL patients is 13.5%. There was no statistically significant associations between positive CD30 expression and clinicopathological characteristics.